Elementary teachers’ understanding of pedagogical content knowledge analysis disaster mitigation: stories from Indonesia - Muhammad Jaya Adi Putra; Daeng Ayub Natuna; Dina Syaflita; Jumili Arianto; Elda Apnes Tiana; Dodi Suryana (Institute of Advanced Engineering and Science, 2024)
The notion of pedagogical content knowledge (PCK) analysis disaster mitigation often been overlooked in the field of elementary school, because many teachers think that it is too early to practice the concept to student. This article attempts to explore elementary teachers’ understanding on PCK analysis. The method adopted in this research is case study. There were 16 elementary school teachers from six different schools in three different cities in province Riau, Indonesia, selected as participants. Data are collected through rubric the observations and interview using a grounded approach. Findings of this study highlight the extent to which elementary teachers are not yet ready to teach disaster mitigation due to their limited content knowledge and understanding of disaster mitigation. The findings also illuminate complexities faced by teachers in PCK in their teaching. The findings need school authorities must incorporate disaster mitigation materials into their teaching curriculum. Schools need to prepare teachers for teaching disaster mitigation by inviting first responders, such as firefighters, emergency service, or officials from National Board for Disaster Management. Finally, the teachers need to improve their understanding of disaster mitigation and their teaching technique to deliver the mitigation materials relevant to the students.